Illuminating colors: regulation of carotenoid biosynthesis and accumulation by light. (June 2017) - Llorente, Briardo; Martinez-Garcia, Jaime F; Stange, Claudia; Rodriguez-Concepcion, Manuel
Graphical abstract: Highlights: Light promotes both carotenoid biosynthesis and storage in most plant systems. Carotenoid accumulation is positively linked to photomorphogenic development. Light signaling pathways were readapted in tomato fruit to sense ripening progression. Orange carrots are photomorphogenic mutants that develop root chloroplasts in the light. Carotenoid contents are strongly influenced by light-modulated plastid identity. Abstract : Light stimulates the biosynthesis of carotenoids and regulates the development of plastid structures to accommodate these photoprotective pigments. Work with Arabidopsis revealed molecular factors coordinating carotenoid biosynthesis and storage with photosynthetic development during deetiolation, when underground seedlings emerge to the light. Some of these factors also adjust carotenoid biosynthesis in response to plant proximity ( i.e., shade), a mechanism that was readapted in tomato to monitor fruit ripening progression. While light positively impacts carotenoid production and accumulation in most cases, total carotenoid levels decrease in roots of colored carrot cultivars when illuminated. The recent discovery that such cultivars might be photomorphogenic mutants provides an explanation for this striking phenotype.